2013
DOI: 10.1371/journal.pone.0059200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli NemA Is an Efficient Chromate Reductase That Can Be Biologically Immobilized to Provide a Cell Free System for Remediation of Hexavalent Chromium

Abstract: Hexavalent chromium is a serious and widespread environmental pollutant. Although many bacteria have been identified that can transform highly water-soluble and toxic Cr(VI) to insoluble and relatively non-toxic Cr(III), bacterial bioremediation of Cr(VI) pollution is limited by a number of issues, in particular chromium toxicity to the remediating cells. To address this we sought to develop an immobilized enzymatic system for Cr(VI) remediation. To identify novel Cr(VI) reductase enzymes we first screened cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 42 publications
2
56
0
1
Order By: Relevance
“…NemA is a versatile NADPH-dependent flavoprotein reductase (old yellow enzyme) capable of reducing a broad range of organic compounds, including electrophiles (quinones, glyoxals, trinitrotoluene) (27) and even inorganic substrates, such as nitrates and chromates (28,34). Considering the diversity of compounds formed by acid treatment of xylose (17,35), it is not surprising that some components of PXV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NemA is a versatile NADPH-dependent flavoprotein reductase (old yellow enzyme) capable of reducing a broad range of organic compounds, including electrophiles (quinones, glyoxals, trinitrotoluene) (27) and even inorganic substrates, such as nitrates and chromates (28,34). Considering the diversity of compounds formed by acid treatment of xylose (17,35), it is not surprising that some components of PXV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NemA reductase activity was measured as the N-ethylmaleimide (NEM)-dependent oxidation of NADPH (27,28) unless stated otherwise. For enzyme assays, cells (50 ml) grown in AM1 xylose broth containing 100 mM morpholinepropanesulfonic acid (MOPS) (pH 7) were harvested by centrifugation at an OD 550 of approximately 1, washed twice with 10 ml of cold potassium phosphate buffer (50 mM; pH 7.0), and resuspended in phosphate buffer (3 ml).…”
Section: Methodsmentioning
confidence: 99%
“…The second report dealt with hexavalent chromium (Cr(VI)) remediation. A Cr(VI) reductase, NemA, was fused to PhaC R.eu for presentation on the granule surface [66]. The study demonstrated that the NemAPhaC enzyme combination-displaying granules together with NADH cofactor-generating enzymes such as glucose dehydrogenase or formate dehydrogenase enabled a high degree of chromium transformation with less depletion of NADH cofactors.…”
Section: Fabrications For Pha Granulesmentioning
confidence: 99%
“…An example for an application which abandons the full spectrum of functionalities of living organisms and concentrates only on relevant mechanisms is the application of chromate reductase coupled on polyhydroxyalkanoate granules, developed by Robins and colleagues. In combination with a cofactor regenerating enzyme 25 this quite "plain" system for ex situ remediation can transform the toxic and unfortunately water soluble industrial waste product hexavalent chromium into a nontoxic state (Robins et al 2013). Systems based on this combination were suggested as an economical and safe solution for remediation of a number of pollutants (e.g.…”
Section: In Vitro Systems As a Sustainable Option For Applications Ofmentioning
confidence: 99%